Point of care affirmability of patient safety criteria at tertiary healthcare level in Peshawar-Pakistan: a cross-sectional evaluation - Basharat Hussain; Sheraz Fazid; Ihtesham Ul Haq; Zia Ul-Haq (Khyber Medical University Journal)
Objective: To evaluate the level of compliance with the World Health Organization’s (WHO) recommended patient safety criteria in tertiary healthcare facilities in Peshawar-Pakistan.